Isoprenylated Phenolic Compounds from Morus macroura as Potent Tyrosinase Inhibitors - Wang, Yifan; Xu, Liangjin; Gao, Wen; Niu, Lixin; Huang, Chunyue; Yang, Peiming; Hu, Xiao (Planta Medica, 2018)
Three new Diels-Alder adducts, macrourins E – G (1–3), one new 2-arylbenzofuran, macrourin H (4), and eight known Diels-Alder adducts (5–12) were isolated from Morus macroura. Their structures were elucidated through extensive analysis of spectroscopic data. The 1H NMR and ECD trends in the determination of the configurations of these Diels-Alder adducts were summarized. The tyrosinase inhibitory activities of all compounds isolated were evaluated, and the new compounds (1–4) as well as the eight known compounds (5–12) were found to be potent with IC50 values ranging from 0.39 to 4.54 µM. Among them, 1 showed the best tyrosinase inhibitory activity with an IC50 value of 0.39 µM, approximately 50 times stronger than the positive control, kojic acid.
Keywords: Morus macroura; Moraceae; Diels-Alder adducts; 2-arylbenzofuran; kojic acid; tyrosinase inhibitory activity